Multicenter phase 2 study of combination therapy with ruxolitinib and danazol in patients with myelofibrosis. (September 2017) - Gowin, K.; Kosiorek, H.; Dueck, A.; Mascarenhas, J.; Hoffman, R.; Reeder, C.; Camoriano, J.; Tibes, R.; Gano, K.; Palmer, J.; Mesa, R.
Highlights: Ruxolitinib associated cytopenias often limit tolerance to therapy. Ruxolitinib and danazol therapy demonstrated hematologic stabilization. Combination therapy did not improve response per IWG-MRT criteria. Therapy was generally well tolerated. Combination therapy may be useful in heavily pretreated MF patients. Abstract: Myelofibrosis is a myeloproliferative neoplasm that is characterized by splenomegaly, profound symptom burden, and cytopenias. JAK inhibitor therapy offers improvements in splenomegaly, symptom burden, and potentially survival; however, cytopenias remain a significant challenge. Danazol has previously demonstrated improvements in myelofibrosis-associated anemia. We conducted a phase II clinical trial evaluating the efficacy and tolerability of combination therapy with ruxolitinib, an oral JAK inhibitor, and danazol. Fourteen intermediate or high-risk MF patients were enrolled at 2 institutions. Responses per IWG-MRT criteria were stable disease in 9 patients (64.2%) clinical improvement in 3 (21.4%) all of which were spleen responses, partial response in 1 (7.1%) and progressive disease in 1 (7.1%). Despite limited IWG-MRT response, stabilization of anemia and thrombocytopenia was demonstrated. In JAK inhibitor naïve patients, 4/5 (80%) had stable or increasing hemoglobin. Of the 9 patients on prior JAK inhibitor, 5 patients (55.5%) and 8 patients (88.9%) had stable or increasing hemoglobin or platelet levels, respectively. Adverse events possibly related included grade 3 or greater hematologic toxicity in ten patients (71.4%) and non-hematologic toxicity in two patients (14.3%). Although combination therapy did not lead to increased hematologic response per IWG-MRT criteria, hematologic stabilization was observed and may be clinically useful.